Barrier Analysis in Implementing Macapat Song Learning as Cultural Preservation - Doni Hermawan; Joko Sukoyo (Journal of Innovation in Educational and Cultural Research, 2023)
This research examines the factors that hinder the implementation of Macapat song learning in junior high schools. This research used a descriptive qualitative approach. Data collection techniques in this research used observation, interview, and documentation techniques. The data was collected and analyzed using data analysis by Miles and Huberman (1994), which began with data collection, data reduction, data presentation, and conclusion. The validity of the data used the triangulation data method. The research results show that the implementation of Macapat song learning in junior high school is hampered by two factors: internal and external factors originating from students and teachers. The internal factors inhibiting students include low student interest, students' lack of mastery of Javanese vocabulary, and the assumption that learning Macapat songs is less critical. The internal factors inhibiting teachers include Javanese language teachers who tend not to have a Javanese language educational background, teachers who do not master the material of Macapat songs, less innovative learning methods, and teachers who have difficulty implementing the emancipated curriculum in learning. The external factors inhibiting students include device usage factors, family factors, and inadequate internet networks. The external factors inhibiting teachers include insufficient allocation of learning hours and lack of infrastructure that supports Macapat song learning. This research expects students to grow their interest in learning Macapat songs to maintain and preserve Javanese culture. With students' seriousness towards the Macapat song learning material, students will have a sense of love for Indonesian culture.